The role of civic education in shaping the character of students at al hikam islamic boarding school, bangkalan - Mas'ud, Mochammad; Eka Indriani, Dian; Sahid, M. (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2024)
Civic Education plays a crucial role in shaping the character of students, providing a moral foundation for building a tolerant and just society. This research focuses on tolerance at Pondok Pesantren Al Hikam Bangkalan, exploring the relationship between civic education and student character. Using a descriptive qualitative approach, this study involved observations and interviews with 10 students. The results show that 80% of students regularly participate in learning activities, all students display respectful behavior towards teachers, and 90% maintain environmental cleanliness. Furthermore, all students refrain from discrimination and respect differences, creating an inclusive and safe social environment. Interviews revealed a strong understanding of Pancasila values and the importance of tolerance. Civic education at Pondok Pesantren Al Hikam has proven effective in shaping students' character to appreciate diversity and the values of tolerance. This research provides valuable insights for the development of policies and practices in civic education at Islamic boarding schools.